2013
DOI: 10.1186/1748-717x-8-250
|View full text |Cite
|
Sign up to set email alerts
|

High-dose stereotactic body radiotherapy correlates increased local control and overall survival in patients with inoperable hepatocellular carcinoma

Abstract: BackgroundRecent studies using stereotactic body radiotherapy (SBRT) for hepatocellular carcinoma (HCC) have reported high tumor response and local control. However, the optimal SBRT dose remains unknown, and it is still not clear whether a dose response relationship for local control (LC) and overall survival (OS) exist or not. We performed this study to determine whether a dose response relationship for LC and OS is observed in SBRT for inoperable HCC.MethodsBetween 2003 and 2011, 108 patients with HCC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
157
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(162 citation statements)
references
References 37 publications
5
157
0
Order By: Relevance
“…In a dose-escalation series on patients with lung and liver metastases (19), the LC was improved on the uni-and multivariate analysis with greater nominal dose, i.e., with greater dose per fraction, since the number of fractions remained constant. A similar observation was reported in patients with hepatocellular carcinoma (20). Timmerman et al (21) observed in a dose-escalation study on early-staged primary lung cancer no treatment failures in patients treated with a dose greater than 18 Gy/fraction.…”
Section: Discussionsupporting
confidence: 59%
“…In a dose-escalation series on patients with lung and liver metastases (19), the LC was improved on the uni-and multivariate analysis with greater nominal dose, i.e., with greater dose per fraction, since the number of fractions remained constant. A similar observation was reported in patients with hepatocellular carcinoma (20). Timmerman et al (21) observed in a dose-escalation study on early-staged primary lung cancer no treatment failures in patients treated with a dose greater than 18 Gy/fraction.…”
Section: Discussionsupporting
confidence: 59%
“…Patients with HCC portal vein thrombosis (PVT), a poor prognostic factor, have been included in several of the above studies [13][14][15][16][17][18]21 where overall outcomes are better than expected. Recanalization of the vascular HCC following SBRT potentially facilitates TACE, which is less effective in the presence of main branch PVT.…”
Section: Sbrt For Portal Vein Thrombosismentioning
confidence: 99%
“…SBRT allows the delivery of higher doses of radiotherapy as compared to 3D-HDCRT, with more accuracy to target the tumor volume and to spare the nontumorous surrounding liver parenchyma. In Jang's et al report 41 , a 3 fraction 51 Gy SBRT (range, 33-60 Gy) led to 87% local control in a dose efficient manner for tumors ranging from 10 to 70 mm, mean 31 mm, median 30 mm (100% in our study, with tumors ranging from 23 to 88 mm, mean 49 mm, median 50 mm). The one, two and three year overall survival rates reached 82%, 63% and 55% respectively, median around 42 months with SBRT vs. 79%, 59% and 44%, median 39.6 months in our TACE+3D-HDCRT study.…”
Section: Discussionmentioning
confidence: 78%